O papel das células de Sertoli na espermatogênese - Monteiro, Claudia Dias [UNESP]; Bicudo, Sony Dimas [UNESP]; Toma, Hugo Shisei [UNESP] (My University, 2010)
The Sertoli cell is an example of cell with specializations structural that carry out several functions simultaneously. They associate at the same time with at least four different types of germinatives cells, propitiating like this conditions for the progression and differentiation of these during the spermatogenesis, with the basal membrane and with other Sertoli cells. The Sertoli cells exercise vital function in the regulation of the spermatogenesis, therefore any dysfunction of these it can cause alterations and or degenerations of the germinatives cells and infertility. The Sertoli cells have several functions as: it controls of the maturation and of the migration of the germinatives cells; synthesis of proteins and steroids, are involved in the control of the passage of the secretions among tubular and interstitial compartments and, they form the hemato testicular barrier. The spermatic production daily for gram of testicle is used as parameter for evaluation of the efficiency of the spermatogenesis and it can be related with: the number of Sertoli cells for gram of testicle, the capacity of support of the Sertoli cell, the volumetric density of the seminific tubules in the testicle (%), the number of spermatogonias generations and to smallest loss of germinatives cells during the spermatogenesis. The objective of this revision is to explain the function of the Sertoli cells in spermatogenesis, since it is made such necessary understanding for evaluations and interpretations of some cases of infertility.

A célula de Sertoli é um exemplo de célula com especializações estruturais regionalizadas que desempenham simultaneamente várias funções. Elas se associam ao mesmo tempo com no mínimo quatro diferentes tipos de células germinativas, propiciando assim condições para a progressão e diferenciação destas durante a espermatogênese, com a membrana basal e com outras células de Sertoli. As células de Sertoli exercem papel vital na regulação da espermatogênese, portanto qualquer disfunção destas pode ocasionar alterações e ou degenerações das células germinativas e infertilidade. As células de Sertoli têm diversas funções como: controle da maturação e da migração das células germinativas; síntese de proteínas e esteróides estão envolvidas no controle da passagem das secreções entre compartimentos tubulares e intersticiais e, formam a barreira hemato-testicular. A produção espermática diária por grama de testículo é utilizada como parâmetro para avaliação da eficiência da espermatogênese e pode ser relacionada com: o número de células de Sertoli por grama de testículo, a capacidade de suporte da célula de Sertoli, a densidade volumétrica dos túbulos seminíferos no testículo (%), o número de gerações de espermatogônias e a menor perda de células germinativas durante a espermatogênese. O objetivo desta revisão é esclarecer o papel das células de Sertoli na espermatogênese, já que se faz necessário tal entendimento para avaliações e interpretações de alguns casos de infertilidade.
The function of sertoli cells in spermatogenesis
Keywords: Sertoli Cells; Spermatogenesis; Spermatozoids; Células de Sertoli; Espermatogênese; Espermatozóides